Peningkatan Kapasitas Kreatif Warga Pekon Way Kerap Mewujudkan Desa Wisata Berkelanjutan - Lisa, Diana; Rusmiati, Fadhilah; Agumsari, Dini; Khotimah, Siti Nurul (FT Universitas Lampung, 2024)
Pekon Way Kerap has extraordinary natural potential such as scenery, the uniqueness of the location which is a transit area for people who are going to or going to the destination will stop by this area. Visits are mainly located at the Imanuddin Mosque at the crossroads and offer beautiful views of the natural atmosphere, making Pekon Way Kerap have the potential to improve infrastructure and supporting facilities in the surrounding area. In addition, the route passed by Pekon Way Kerap is also a tourist route to the Tanjung Setia surfing object location located on the West Coast. Right on the east side of the mosque opposite the location, there is a village of native Lampung people, a settlement with a distinctive appearance of a stage building nuance sprinkled with a variety of beautiful building ornaments, displaying the exotic atmosphere of the area. The settlement is in the form of a stage, as an original/initial building and is still maintained in the future, the sustainability of the existence of a stage building with the uniqueness of the native tribe of Pekon Way Kerap as Kampung Tuha. Increasing the creative capacity of local residents by utilizing the technology era and driven by the fulfillment of facilities, such as internet networks, increasing skills, innovation in the use of creativity requires support from all parties, while maintaining noble values is always an emphasis in running life, as a development of the latest innovations. increasing the flow of information, the more advanced technology, the more we race side by side together to increase potential. The activity aims to explore information, conclude the concept of fulfilling the requirements as a sustainable tourism village. By using qualitative descriptive methods to find out and convey it is hoped that it can meet, solve problems at the activity location. Located in Pekon Way Kerap, Semaka District, Tanggamus Regency. The results of the activity in the form of formulating the idea of the concept of strengthening the creative capacity of residents towards sustainable tourism villages.